Individual and synergistic toxic effects of carbendazim and chlorpyrifos on zebrafish embryonic development. (October 2021) - Fan, Ruiqi; Zhang, Wanjun; Li, Lizhong; Jia, Li; Zhao, Jun; Zhao, Zengming; Peng, Shuangqing; Yuan, Xiaoyan; Chen, Yiqiang
Abstract: The fungicide carbendazim and the insecticide chlorpyrifos are frequently used together to protect various fruit and vegetable crops in China. At high doses, carbendazim is a known carcinogen while chlorpyrifos has neurotoxic potential, but the combined toxicity of these two compounds has not been systematically investigated. In this study, we examined the separate and combined effects of these compounds on zebrafish embryonic development. The LC50 values for carbendazim and chlorpyrifos at 96 h post-fertilization (hpf) were 0.89 mg/L and 3.83 mg/L, respectively. Carbendazim dose-dependently increased the spontaneous tail-wagging frequency of 24 hpf embryos, the hatching rate of 48 hpf embryos, and the mortality and deformity rate of 96 hpf embryos, while chlorpyrifos increased the heart rate of 48 hpf embryos as well as the mortality and deformity rate of 96 hpf embryos. Mixed exposure at an equipotent concentration ratio (Mix1) and at the ratio of maximum residue limits for typical fruits (apples) (Mix2) revealed significant synergistic effects on lethality at 96 hpf within the 0%–90% effect levels range. In contrast, there was an antagonistic effect of the equipotent concentration ratio on lethality in the 90%–100% concentration range, while the ratio at the maximum residue limits still showed a synergistic effect. Mix1 exhibited antagonism on hatching rate in the 0%–35% range and synergy in the 40%–100% range, while Mix2 had a synergistic effect on hatching rate in the 0%–35% range, an additive effect at 40%, and an antagonistic effect at >40%. Both mixtures had a synergistic effect on deformity rate over all concentration ranges. Carbendazim and chlorpyrifos demonstrate synergistic developmental toxicity, indicating that health and environmental risk assessments should be conducted for various combinations of these agents. Highlights: We examined carbendazim and chlorpyrifos toxicity in zebrafish embryos. Both pesticides dose-dependently disrupted embryonic development. In combination, toxicity was primarily synergistic across dose ranges and ratios. Comprehensive health risk evaluation must consider these complex combined effects.